Integrated agriculture: not an option but an imperative - Lightfoot, Clive (Technical Centre for Agricultural and Rural Cooperation, 1996)
Dr Clive Lightfoot is Director of the Information Centre for Low External Input and Sustainable Agriculture (ILEIA) in the Netherlands, a post he took up in 1995. Previously he was Head of Integrated Resources Management at the International Centre...